Purkinje cell loss in essential tremor: Random sampling quantification and nearest neighbor analysis. Issue 3 (10th February 2016) - Choe, Matthew; Cortés, Etty; Vonsattel, Jean‐Paul G.; Kuo, Sheng‐Han; Faust, Phyllis L.; Louis, Elan D.
ABSTRACT: Introduction: Purkinje cell loss has been documented in some, although not all, postmortem studies of essential tremor. Hence, there is considerable controversy concerning the presence of Purkinje cell loss in this disease. To date, few studies have been performed. Methods: Over the past 8 years, we have assembled 50 prospectively studied cases and 25 age‐matched controls; none were reported in our previous large series of 33 essential tremor and 21 controls. In addition to methods used in previous studies, the current study used a random sampling approach to quantify Purkinje cells along the Purkinje cell layer with a mean of 217 sites examined in each specimen, allowing for extensive sampling of the Purkinje cell layer within the section. For the first time, we also quantified the distance between Purkinje cell bodies—a nearest neighbor analysis. Results: In the Purkinje cell count data collected from fifteen 100 × fields, cases had lower counts than controls in all three counting criteria (cell bodies, nuclei, and nucleoli; all P  < 0.001). Purkinje cell linear density was also lower in cases than controls (all P  < 0.001). Purkinje cell linear density obtained by random sampling was similarly lower in cases than controls in all three counting criteria (cell bodies, nuclei, and nucleoli, all P  ≤ 0.005). In agreement with the quantitative Purkinje cell counts, the mean distance from one Purkinje cell body to another Purkinje cell body along the Purkinje cell layer was greater in cases than controls ( P  = 0.002). Conclusions: These data provide support for the neurodegeneration of cerebellar Purkinje cells in essential tremor. © 2016 International Parkinson and Movement Disorder Society